Contribution of ABCB1 gene polymorphisms to breast cancer cells response to chemotherapy - Hołysz, Hanna; Rubiś, Błażej (Menopause Review/Przegląd Menopauzalny, 2013)
Each year about 11,000 new breast cancer cases are recognized and almost half of these people die. Such great mortality may result from too late diagnosis, lack of specific and efficient drugs and multidrug resistance (MDR) observed in cancer cells. The basic mechanism triggering multidrug resistance is an increased expression and activity of membrane transporters that mostly belong to the ABC superfamily (ATP binding cassette). Among those proteins, glycoprotein P ( ABCB1 gene expression product) is the best known one. The substrate spectrum of glycoprotein P is very broad and contains xenobiotics and cytotoxic drugs, protein inhibitors, immunosuppressive agents, steroids, statins, calcium channel blockers, beta-blockers, antihistamine drugs, antidepressants and antiemetic drugs. In these gene sequences, numerous polymorphisms were described and especially three of them reveal great clinical significance: cytosine into thymine transition in 1236 position of exon 12 – (C1236T, rs1128503), substitution in exon 21 – G2677A/T (rs2032582) and in exon 26 – C3435T (rs1045642). Those polymorphisms may affect ABCB1 expression (C3435T), glycoprotein P structure (G2677T/A) or protein capability to bind substrates (C1236T). It is suggested that consequently these polymorphisms may modify the chemotherapy response in cancer cells. In this review we describe the modulating effect of ABCB1 gene polymorphisms in breast cancer chemotherapy.